Mitos de género en torno a la cobertura de noticias de femicidios diario extra - Naranjo San Lucas, Karla Alexandra (2020)
This research project focuses on the study of a present and feasible comparison, whose purpose is to analyze how the media contributes to strengthening the genres and myths that determine the damage within the country, the news that the written press addresses are situations of violence or femicide. An observation was made, the reproduction of myths and stereotypes about women in this study is carried out in particular the dam; It is very common information that rife among others. Each of the topics was exposed in detail, but limiting the information only with the direct relationship of the subject of the study, so that a clear understanding was obtained with the points being treated and in order to achieve the objectives that were established. Thanks to the results analysis, it is possible to observe the point of view that arises in the methodology of the media to establish a story. Thus, it was allowed to make the conclusions that supported or rejected the established hypotheses. This thesis is presented as a study that can provide the guideline for other studies related to this topic; since the femicide of the woman, besides being very wide, allows to extend the study. In the same way that can be taken as a basis for studies of femicides, violence, homicides, gender, stereotypes among many others.